ANCIENT TOMBS, TRACES OF INTANGIBLE CULTURAL HERITAGE, AND ETNOPRENEURSHIP: THE CASE OF THE TOMB OF SHEIKH JA'FAR SHIDDIQ CIBIUK GARUT, WEST JAVA - Iim Imadudin; Lia Nuralia (International Conference on Social and Islamic Studies, 2021)
This study aims to reveal archaeological objects and sustainable traditions at the tomb of Sheikh Muhammad Ja'far Siddiq in Cibiuk Garut. Sheikh Ja'far was a muslim religious leader who spread Islam in the late 17th and early 18th centuries in Garut. The research method used is the archaeological research method. The technique of collecting data in the field is through observation to determine the existence of objects, situations, contexts, and their meanings. The data obtained for this paper was obtained through a researchconducted in 2021 at the tomb site complex of Sheikh Ja'far Shiddiq in the Cibiuk Garut area. In addition toobservation, archaeological and historical data were obtained through literature studies and interviews. Thisstudy uses an anthropological religion and folklore. The traces of Sheikh Muhammad Ja'far Shiddiq are notonly in the form of tombs and mosques, but also collective memories of the spread of Islam in Garut andstories about one of the popular intangible cultural heritage in Priangan West Java, namely